First-principles calculations of zone center phonons and related thermal properties of MgSiN2 - Chaiyawat Kaewmeechai (2018)
© Published under licence by IOP Publishing Ltd. MgSiN2semiconductor is alternative material beyond the family of III-N, which is used widely in optoelectronic devices. This work presents the calculations of the dielectric tensor, Born effective charge tensor, phonon frequencies at Γ point, phonon dispersion, Helmholtz free energy (ΔF), internal energy (ΔE), entropy (ΔS) and specific heat capacity at constant volume (Cv) of MgSiN2by using the density-functional perturbation theory (DFPT) as implemented in ABINIT. We found that the phonons and thermal properties of MgSiN2have similar properties to those of ZnSiN2and Cvof MgSiN2are in agreement with the available experimental results.